Особливості корекції фізичного стану дітей з порушенням розумового розвитку - Лістау, Карина; Доцюк, Лідія (https://journals.indexcopernicus.com/search/details?id=49506&lang=en, 2020)
Adaptive physical culture for children with developmental disabilities should be considered as a corrective-compensatory and therapeutichealth form of influence on motor impairment, as a means of re-adaptation of motor disorders. The content of corrective-adaptive work with children with mental retardation is to identify typical violations of the technique of performing basic movements, selection of means and methods of correction of violations of the technique of performing basic movements, development of physical qualities, formation and correction of motor skills. In children with mental retardation, there are movement disorders, which are not peculiar to normally developed preschool children. That is why the technique of performing basic movements in children with mental retardation should be evaluated by parameters that characterize the features of their motor activity. As a result of studies, it was found that while walking and running, children bend or rotate their torso, tilt their heads, incorrectly put their feet, carry out “weak” repulsion and removal of the thigh of the leg. The movements of hands and feet are not coordinated, there is a deviation from a given direction of movement, disturbance of the rhythm of movements. After using the complex of adaptive physical culture, improvement of some indicators of speed qualities and coordination abilities – “jogging by 30 m”, “rhythm of hand movements” and “precision of fine motor skills” was established. Indicators of coordination abilities “coordinated rhythm play” and “equilibrium” remained unchanged, although in the individual dynamics of the results there was a clear increase in values. The correction of the basic motor actions, carried out by the method used, provided a reliable increase in the indicators of the development of throwing, long jump from a place, walking, running, in contrast to the results of the control group, which recorded a significant increase only in the indicator of the development of running.
Keywords: children of preschool age, mental retardation, correction of motor disorders, motor skills, physical activity